Does board diversity affect institutional investor preferences? Evidence from Latin America (2018)
This paper enquires whether institutional investors have specific preferences on the composition of the board of directors in Latin American firms they hold shares in. The result show that preferences vary significantly in terms of the type of institutional investor. The econometric results suggest grey institutional investors (pension funds and insurance companies) prefer experience and education, while dislike CEO entrenchment. Independent institutional investors value more directors' professional experience i.e., former CEOs and founders of any firm. Grey investors are more concern on firm corporate governance mechanisms consistent with the agency view, while independent investors are focused in business opportunities in accordance with the resource-based-view of board of directors.